Designing an intellectual property management information system for the University of the Philippines Manila Technology Transfer and Business Development Office - Llamzon, Roxanne B. (University of the Philippines Diliman, 2017)
It is imperative for the University of the Philippines (UP) to facilitate the dissemination of research outputs and innovations generated by its faculty and students. Technology transfer is the primary mechanism to fulfill UP's mandate to be both a research-intensive and public service-oriented national university. The audit and protection of intellectual property assets are the first steps to not only successful technology transfer, but also to building an innovation ecosystem in the university.